Ferramenta de auxílio para aprendizagem do Português - Miguel Agostinho Santos Nunes (2017)
It's increasingly important to use verbal and non-verbal language correctly as means of communication since it allows access to knowledge and social and personal development.The process of learning to read and write begins immediately in preschool education. This process is very complex given all the characteristics and rules of the Portuguese language and because the linguistic, mental, motor, emotional and social development occur in parallel and are dependent on each other. Over the years, the teaching profession incurs the risk of routine, ineffective and uninteresting practices, both for the children and for the education professionals themselves. It's necessary to introduce new ways of teaching more dynamic, systematic, interesting and motivating in a way that it's more adapted to the learning curve of each student and less susceptible to human error by education professionals. Therefore, it's important to minimize and correct the learning errors from the beginning.A poor learning of reading and writing makes the progress of the student in the various school levels harder. As these two mechanisms are the main channels of knowledge share and acquisition, a student who presents difficulties at this level will incur the risk of being retained in the same school year more than once. Furthermore, learning problems not only cause academic and communication failures, but also low self-esteem with consequent disturbances in social and emotional development. When a student finishes his academic life, his level of Portuguese knowledge may be a barrier to a job application. In addition, another problem is related with the cost that each student represents for the Portugal government, this cost increases with the years needed to complete the minimum required education level.In this work, it's intended to develop an Android application to help in the process of learning Portuguese. The use of computational tools to aid learning tends to combat failures in this process: demotivation; errors arising from routine practices used by teachers; inadequacy of the learning curve for each student; lack of family experiences that stimulate the learning of writing and reading. The application has two levels of learning with exercises ranging from stroke training with the pen to learning letters, words and sentence construction. The exercises are in accordance with curricular goals established by the ministry of education. In parallel with the teaching of Portuguese, there will be a battery of exercises for screening neurological problems associated with a delay in the learning growth curve. The application differs from the textbooks for the ability to correct the exercises and indicate to the student the main mistakes made and points to be improved. To be able to use the application by children who can't read, sound is used to explain exercises and existing contents. As the student solves exercises, statistics and other important information are collected so that the teacher is aware of the evolution and main difficulties. In addition, this information is useful to adapt the difficulty of the proposed exercises and try to keep the student motivated.